2020
DOI: 10.3390/nu12113493
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition Prevalence according to the GLIM Criteria in Head and Neck Cancer Patients Undergoing Cancer Treatment

Abstract: Malnutrition is highly prevalent in people with head and neck cancer (HCN) and is associated with poorer outcomes. However, variation in malnutrition diagnostic criteria has made translation of the most effective interventions into practice challenging. This study aimed to determine the prevalence of malnutrition in a HNC population according to the Global Leadership Initiative on Malnutrition (GLIM) criteria and assess inter-rater reliability and predictive validity. A secondary analysis of data available for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 37 publications
4
35
2
1
Order By: Relevance
“…Within healthcare system outcomes, mortality was reported most frequently (n ¼ 33; 27%) [16,22,23,25,26,28e31, 34,37e42,44,45,53,55,57,60,61,65,67,68,73e75,80,83,85,89]. Other outcomes were hospitalization/readmissions/costs (n ¼ 11; 9%) [27,29,34,38,44,62,67,69,83,85,91], hospital and/or intensive care unit LOS (n ¼ 10; 8%) [27,34,44,53,65,67,77,83,91], complications (n ¼ 7; 6%) [53e55, 68,72,85], critical care admission (n ¼ 2; 2%) [42,67], and institutionalization (n ¼ 2; 2%) [16,29]. Patient outcomes included sarcopenia (n ¼ 6; 5%) [17,18,24,35,38,93], physical function (n ¼ 5; 4%) [38,57,75,80,93], quality of life (n ¼ 5; 4%) [56,59,64,74,75], falls/fractures (n ¼ 3; 2%) [29,38], frailty (n ¼ 2; 2%)…”
Section: Discussionmentioning
confidence: 99%
“…Within healthcare system outcomes, mortality was reported most frequently (n ¼ 33; 27%) [16,22,23,25,26,28e31, 34,37e42,44,45,53,55,57,60,61,65,67,68,73e75,80,83,85,89]. Other outcomes were hospitalization/readmissions/costs (n ¼ 11; 9%) [27,29,34,38,44,62,67,69,83,85,91], hospital and/or intensive care unit LOS (n ¼ 10; 8%) [27,34,44,53,65,67,77,83,91], complications (n ¼ 7; 6%) [53e55, 68,72,85], critical care admission (n ¼ 2; 2%) [42,67], and institutionalization (n ¼ 2; 2%) [16,29]. Patient outcomes included sarcopenia (n ¼ 6; 5%) [17,18,24,35,38,93], physical function (n ¼ 5; 4%) [38,57,75,80,93], quality of life (n ¼ 5; 4%) [56,59,64,74,75], falls/fractures (n ¼ 3; 2%) [29,38], frailty (n ¼ 2; 2%)…”
Section: Discussionmentioning
confidence: 99%
“…This study is a secondary data analysis using the collected data from two multicentre observational point prevalence studies (PPS) conducted in 2016 and 2018, with the methodology previously reported [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…To utilize GLIM, clinicians need one criterion met from both the phenotypic and etiologic categories to adequately diagnose PCM. Researchers attempting to validate the GLIM tool in patients with head and neck cancer found that the GLIM diagnosis of PCM was significantly associated with BMI but was not predictive of 30‐day hospital readmission 36 . Efforts for the validation of GLIM are ongoing.…”
Section: Malnutrition Nutrition Assessment Toolsmentioning
confidence: 99%